Supply Chain Management to Improve the Distribution Efficiency of Puli Crackers in UD. Gangsar Jaya Lumajang - Emmy Ermawati (LPPM of NAROTAMA UNIVERSITY, 2021)
Purpose: Improving the Distribution of Puli Crackers in UD. Gangsar Jaya Lumajang Design/methodology/approach: The method used is an ethnographic approach starting from the collection of literature sources and supported by field data. Findings: The results of the study show that the supply chain within the company is very possible to achieve increased efficiency in the distribution process of the home industry. Research limitations/implications: This research implication of problems and solutions of supply chain distribution in UD. Gangsar Jaya Lumajang. Practical implications: This research can be used as input for stakeholders to be used as a reference in optimizing the creative industry. Originality/value: This paper is original Paper type: Research paper